The immunology of experimental liver transplantation in the rat. - Kamada, N (1985)
In many species, the rejection of liver allografts is milder than that of other organs. This is especially so in the rat where, without immunosuppressive treatment, liver grafts between certain strain combinations are accepted permanently, whereas skin, heart and renal allografts undergo acute rejection. Reliable surgical methods, together with the availability of inbred strains and a rapidly developing knowledge of its MHC and immune system in general, have made the rat a prime species in which to study the immunological events which follow liver grafting. In non-rejector combinations, liver allografts possess remarkable properties of tolerance induction and antigen-specific immunosuppression, leading to a state of donor-specific unresponsiveness in which grafts of other organs are also accepted. Moreover, liver transplantation can terminate ongoing rejection reactions in other organs and convert an existing state of sensitization against donor antigens into one of unresponsiveness. This review describes recent progress in understanding the immunological mechanisms behind these phenomena. The topics discussed include the rat MHC (RT1) antigens and their distribution in the liver; the genetic control of rejection and non-rejection, including the role of MHC-linked immune response genes; and cellular and humoral mechanisms involved in tolerance and immunosuppression, such as clonal deletion of alloreactive lymphocytes and antibody-mediated enhancement.